GREEN FUNCTION (Comprehensive Journal of Science, 2025)
The green function theory was developed by the scientist George Green 1793-1841 and is a mathematical function. Where this theory was developed to improve and manage ordinary and partial differential equations with different dimensions and for a time-dependent and time-independent problem .The theory was also developed to serve physics and mechanics, largely in quantum field theory and thermodynamics, as well as in statistical field theory. Thus, during the understanding and analysis of the theory of green function, its role and importance in science were shown, and many applications were presented to understand it, such as i.e. Boundary and Initial Value problem, Wave Equation, Kirchhoff Diffusion Equation, Diffraction Theory, Helmholtz Equation and etc.So the green function have many important roles in many aspect of sciences, so we try to cover the theory from all of it's aspect.